1998
DOI: 10.1038/bjc.1998.394
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro radiosensitivity of human head and neck cancers

Abstract: Summary A study was made of the intrinsic radiosensitivity of 140 biopsy and surgical specimens of malignant head and neck tumours of different histologies. Using a soft-agar clonogenic assay, the material was assessed for the ability to grow in culture (colony-forming efficiency; CFE) and inherent tumour radiosensitivity (surviving fraction at 2 Gy, SF2). The success rate for obtaining growth was 74% (104/140) with a mean CFE of 0.093% (median 0.031) and a range of 0.002-1.3%. SF2 was obtained for 88 of 140 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…This assumption is consistent with previous studies where these parameters are usually assumed to follow a normal distribution (Jones and Dale, 1999). Normally distributed values of α and β can lead to a skewed distribution in x rt , consistent with published data (Björk-Eriksson et al, 1998).…”
Section: Accepted Manuscript 17supporting
confidence: 92%
“…This assumption is consistent with previous studies where these parameters are usually assumed to follow a normal distribution (Jones and Dale, 1999). Normally distributed values of α and β can lead to a skewed distribution in x rt , consistent with published data (Björk-Eriksson et al, 1998).…”
Section: Accepted Manuscript 17supporting
confidence: 92%
“…Since the parameters of the distribution are derived from fitting to the real clinical data, this is a plausible result. It is also consistent with published data of intrinsic tumour cell radiosensitivity (West et al, 1993;Bjork-Eriksson et al, 1998), and normal fibroblast sensitivity (Peacock et al, 2000). Although these distributions are often considered to be Gaussian, measurements indicate that in reality they are typically slightly skewed.…”
Section: Radiation Sensitivitysupporting
confidence: 87%
“…The majority of these studies used generic or population averages for the biological parameters required for BED calculation, the intrinsic radiosensitivity (SF 2 ), a and a/b, and the potential tumour doubling time (T pot ). In reality, however, tumours are characterised by a broad range of radiosensitivities and consequently different a and b values [7]. Similarly, it has been shown that T pot also varies between tumours with the same histology [8,9].…”
mentioning
confidence: 99%